2018
DOI: 10.1590/0100-6991e-20181793
|View full text |Cite
|
Sign up to set email alerts
|

Perception of body image by patients undergoing bariatric surgery

Abstract: Objective: to investigate changes in body image perception in patients undergoing bariatric surgery, evaluating the accuracy/inaccuracy in body size estimation and satisfaction/dissatisfaction with own body after surgery. Methods: we performed a survey at the General Surgery outpatient clinic of the Clinics Hospital of the Federal University of Pernambuco. Thirty-six patients aged 18 years and older undergoing bariatric surgery participated. We carried out cross-sectional and quantitative studies using the Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 13 publications
1
6
1
18
Order By: Relevance
“…Even with mirror evaluation, the literature has showed that ex-obese patients show a poorer estimation of their shapes compared to peers with the same BMI [54], as well as the impaired ability to notice weight gain in realistic 3D human models which represent themselves [55]. This impaired ability to update body image memory in OS patients could be explained by a sort of weight category bias, with OS patients that stopped to identify themselves as obese, a situation that they could linked to psychological burden situations, worsened by interpersonal problems, chronic stress, or anxiety [56]. This could have a significant implication for public health, because OS patients seem to be incapable of identifying weight changes after massive weight loss, as well as they seem to be into a weight category bias with a cognitive dissonance that could have a role in the weight reduction outcome, if it does not fit their goals [53].…”
Section: Discussionmentioning
confidence: 99%
“…Even with mirror evaluation, the literature has showed that ex-obese patients show a poorer estimation of their shapes compared to peers with the same BMI [54], as well as the impaired ability to notice weight gain in realistic 3D human models which represent themselves [55]. This impaired ability to update body image memory in OS patients could be explained by a sort of weight category bias, with OS patients that stopped to identify themselves as obese, a situation that they could linked to psychological burden situations, worsened by interpersonal problems, chronic stress, or anxiety [56]. This could have a significant implication for public health, because OS patients seem to be incapable of identifying weight changes after massive weight loss, as well as they seem to be into a weight category bias with a cognitive dissonance that could have a role in the weight reduction outcome, if it does not fit their goals [53].…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Além dos benefícios constatados ao nível das PIC, depressão e baixa autoestima, a evidência reunida refere que também a ideação suicida revela melhorias significativas após o tratamento. 1,34,45 A nível físico -metabólico, a CB pode ainda refletir -se na redução da dor, melhoria da mobilidade e das comorbilidades relacionadas com a obesidade (tais como diabetes mellitus e outros fatores de risco cardiovascular, traduzindo -se numa redução dos medicamentos diariamente administrados), melhoria da fertilidade e numa redução da mortalidade global de 23% -40%. 45 -47 Foi estabelecida uma associação favorável entre melhores outcomes cirúrgicos e fatores como idade jovem e altos níveis de cooperação terapêutica.…”
Section: Resultados a Mudanças Na Perceção Da Imagem Corporal E Saúde Mental Após Cirurgia Bariátricaunclassified
“…57 Avaliando a silhueta corporal num grupo de doentes após CB, Lacerda et al (2018) constataram que apenas 11,8% das mulheres se mostraram satisfeitas com o resultado, comparativamente a 50% dos doentes masculinos satisfeitos; evidenciou -se ainda que, embora a CB tenha diminuído significativamente o IMC, a maioria dos doentes continuava a autoconceber -se com aparência de maior volume corporal do que o volume real correspondente. 1 A percentagem de IMC recuperado após cirurgia, a ingestão alimentar compulsiva e a preocupação com a IC são os fatores que explicam 50% da variância da sintomatologia depressiva após a cirurgia, correspondendo as PIC ao fator com impacto mais significativo. 58 Alguns autores afirmam que o doente possui uma crença de que a CB constituirá a solução dos seus problemas, iniciando uma busca por um corpo sonhado e idealizado que, na maioria das vezes, não se concretiza; este corresponderá, então, a um momento circunstancial propício ao surgimento de PIC.…”
Section: Resultados a Mudanças Na Perceção Da Imagem Corporal E Saúde Mental Após Cirurgia Bariátricaunclassified
See 1 more Smart Citation
“…8,22 Similarly, body image dissatisfaction and depression in postbariatric patients are associated with less weight loss 23 and can result in regaining of the weight that was lost, nutritional deficiencies, and even increased risk of death. 24,25 Considering these findings authors suggest that body image should be considered an outcome parameter in assessing health-related quality of life in patients undergoing bariatric surgery. 23,26 It has also been noted that further study to find interventions that increase body satisfaction would be of great value to the field.…”
Section: Introductionmentioning
confidence: 99%